Successful Use of Negative Pressure Wound Therapy for Abdominal Wall Necrosis Caused by a Perforated Ascending Colon Using the ABThera System - Kouki Imaoka; Takuya Yano; Yasuhiro Choda; Ko Oshita; Yuma Tani; Tetsushi Kubota; Michihiro Ishida; Daisuke Satoh; Masanori Yoshimitsu; Kanyu Nakano; Masao Harano; Hiroyoshi Matsukawa; et al. (Case Reports in Surgery)
Background. The practice of leaving the abdomen open after an emergency laparotomy has gained increasing popularity recently. Negative pressure wound therapy (NPWT) is known as an effective technique in the management of an open abdomen (OA). A new device, the ABThera™ Open Abdomen Negative Pressure Therapy System (KCI USA, San Antonio, TX, USA), was specifically designed to achieve a temporary abdominal closure (TAC) in the management of an OA. This study was aimed at presenting a successful experience of treating a case of abdominal wall necrosis caused by a perforated ascending colon using the ABThera System. Case Presentation. A 66-year-old man was admitted to our hospital with complaints of severe pain in the abdomen. On admission, abdominal contrast-enhanced computed tomography (CT) showed fluid collection, an air pocket in the subcutaneous fat layer of the abdominal wall, and edematous changes in the adipose tissue in the peritoneum and abdominal wall. Based on a diagnosis of peritonitis resulting from a perforated ascending colon, emergency surgery was performed. A right hemicolectomy, ileostomy construction, and debridement of the necrotic tissues were performed. However, necrotizing fasciitis rapidly spread; therefore, more necrotic tissue was debrided in a second operation. The abdominal wall defect was left open, and the ABThera System was used in the management of the OA; this device promoted wound healing. A reduction was observed in the size of the open wound with visible granulation tissue. The defect was finally covered with a mesh split-thickness skin graft and anterolateral thigh flap. Conclusions. In the management of a case of a massive wound with infection, it can be of great benefit to treat the wound with NPWT initially to decrease its size. The ABThera System could facilitate early and safe management of an OA by surgeons.